الخلع وأحكامه بين القانون الإيراني والمذاهب الأربعة : دراسة تحليلية - دادخدا، سميه (al-Jami'ah al-Islamiyah al-'Alamiyah, 2017)
This study focuses on the comparison between Iranian law and the four Madahib with regard to the laws of Khul'. The aim of this research is to highlight the differences between Iranian law and the four Madahib. This comparison aims to narrow the gap between these two laws with regard to Khul', and to improve the issues regarding woman's rights in Khul' that the Iranian law neglects. This is done by the method of induction using different references that are related to this topic. This research also uses an analytical method to view different opinions that are supported by evidence and a comparative method to compare between Iranian law and the four Madahib. Results were obtained from this research, in particular, that the Khul' is a divorce and is not an annulment. Hence, it has the same consequences as a divorce, and the Raj'ah is the right of the woman. The man has no power over the Raj'ah. Furthermore, this method is appropriate for a woman who dislikes her husband and fulfills the requirements of Khul'. Therefore, with the use of Khul' the wife can separate from her husband if she finds that it would be difficult to continue her marital life with him. She can specify a compensating amount that would be agreed upon between the two parties and this amount would be less, equal to, or more than Mahr. This amount could be in the form of money, provided that the amount is valuable and proprietary, and that is consensus between the four Madahib and Iranian law. However, the pillars of Khul' in Iranian law differ from those of the four Madahib. It has two pillars in Iranian law which are the wife and the compensation. On the other hand, it has four pillars in the four Madahib which are the husband, the wife, the compensation and the form.